Effect of an Echinacea-Based Hot Drink Versus Oseltamivir in Influenza Treatment: A Randomized, Double-Blind, Double-Dummy, Multicenter, Noninferiority Clinical Trial - Karel Rauš; Stephan Pleschka; Peter Klein, MSc; Roland Schoop, MSc; Peter Fisher (Elsevier, 2015)
Background: Echinacea has antiviral activity against influenza viruses in vitro and has traditionally been used for treatment of colds and flu. Objectives: This randomized, double-blind, double-dummy, multicenter, controlled clinical trial compared a new echinacea formulation with the neuraminidase inhibitor oseltamivir, the gold standard treatment for influenza. Methods: Following informed consent, 473 patients with early influenza symptoms (≤48 hours) were recruited in primary care in the Czech Republic and randomized to either 5 days of oseltamivir followed by 5 days of placebo, or 10 days of an Echinacea purpurea-based formulation called Echinaforce Hotdrink (A. Vogel Bioforce AG, Roggwil, Switzerland). The proportion of recovered patients (influenza symptoms rated as absent or mild in the evening) was analyzed for noninferiority between treatment groups using a generalized Wilcoxon test with significance level α = 0.05 (2-sided) and using a CI approach in the per-protocol sample. Results: Recovery from illness was comparable in the 2 treatment groups at 1.5% versus 4.1% after 1 day, 50.2% versus 48.8% after 5 days, and 90.1% versus 84.8% after 10 days of treatment with Echinaforce Hotdrink and oseltamivir, respectively. Noninferiority was demonstrated for each day and overall (95% CI, 0.487-0.5265 by generalized Wilcoxon test). Very similar results were obtained in the group with virologically confirmed influenza virus infections and in a retrospective analysis during the peak influenza period. The incidence of complications was lower with Echinaforce Hotdrink than with oseltamivir (2.46% vs 6.45%; P = 0.076) and fewer adverse events (particularly nausea and vomiting) were observed with Echinaforce Hotdrink. Conclusions: Echinaforce Hotdrink is as effective as oseltamivir in the early treatment of clinically diagnosed and virologically confirmed influenza virus infections with a reduced risk of complications and adverse events. It appears to be an attractive treatment option, particularly suitable for self-care. Clinical trial identifier: Eudra-CT: 2010-021571-88. (Curr Ther Res Clin Exp. 2015; 77:66-72)